The Legend of Namartua Limang in Urat Village, Palipi District, Samosir Regency: A Psychological Study - Depri Juliadi Parhusip; Rosita Ginting (Journal of Language Development and Linguistics, 2023)
This article is entitled "The Legend of Namartua Limang in Urat Village, Palipi District, Samosir Regency: A Study of Literary Psychology." The legend of Namartua Limang is a story originating from Suhutnihuta Pardomuan Urat Village. Which tells of a king named Amparhutala Pandiangan who had an abundant rice harvest, which was desired by King Pardindingan. The method used in writing this thesis is the descriptive method. analyzed using structural theory along with the theory of literary psychology. The structural theory includes the intrinsic elements of the Legend of Namartua Limang, including: theme, plot, background or setting, characterization, point of view, and mandate.